Clima ético corporativo: una aplicación del modelo de Víctor y Cullen en las empresas del estado de Sao Paulo - Ferrato, Elio (2005)
Victor and Cullen (1988) developed an empirical survey in order to measure the ethical climate in the organizational bases of 872 employees of four North-American companies. Based on some of the parameters pointed out by these authors, this study had the objective of analyzing ethical corporate climates in nine Brazilian organizations, located in the São Paulo State, Brazil, involving 2573 employees. The Brazilian survey suggested the existence of distinct types of ethical climate and a differentiation in function of norms spread out by the board of directors in the organizations. It was not the purpose to establish a theory about ethical climate, as done by Victor and Cullen, nevertheless, implications of ethical corporate climate in organization theories have been discussed.